PENGARUH PROMOSI TERHADAP MINAT BELANJA ONLINE MELALUI KEMAJUAN TEKNOLOGI INTERNET DI KOTA BLITAR - Latifah, Nunuk; Ike Wardani, Shanti (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
This article is done to find out and analyze the influence of promotion on interest in online shopping through the advancement of internet technology in Blitar City. The sample used was 150 respondents randomly from the general population of the City of Blitar which included 3 Subdistricts namely Sukorejo, Kepanjen Kidul and Sananwetan without any age, education, employment and other specifications due to the limitations of the researchers. The results of structural equestion modeling analysis show that the promotion carried out by online sellers in Blitar City through social media and the internet has given a tendency to influence the advancement of online technology by 28.7%. The promotion of products that exist in most social media or internet by product sellers has a tendency to influence the interest in online shopping in Blitar City by 47.1% and the advancement of online technology has provided a tendency to influence online shopping interest by 32.3%.